THE USE OF PROBLEM SOLVING MODEL IN THE MATERIAL OF THE GENETIC INFORMATION FLOW TO IMPROVE THE STUDENTSâ CONCEPT MASTERY - Supriyanti, F. M. T.; -, Hernani; Mulyanti, S. (Jurnal Pendidikan IPA Indonesia, 2015)
The purpose of this research was to determine the implementation of the IDEAL (Identify, Define, Explore, Anticipat and Act, Looking Back and Learn) problem solving model of Bransford (1998) on the lecture material flow of genetic information, its influence on the mastery of conceps. The method uses quasi-experimental research with pretest-posttest nonequivalent control design. The results of the research show that : (1) the lecture model of problem solving IDEAL on the material flow of genetic information can implemented very well in each stage; (2) had a significant influence on student mastery of concepts; (3) in each of the indicators developed, the experimental class, it is known that the lectures with a problem-solving model of the flow of information on the subject of genetically high yield category on several indicators; (4) gives effect to the problem solving ability of students.Â